2016
DOI: 10.1002/jor.23243
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐body vibration induces pain and lumbar spinal inflammation responses in the rat that vary with the vibration profile

Abstract: Whole-body vibration (WBV) is linked epidemiologically to neck and back pain in humans, and to forepaw mechanical allodynia and cervical neuroinflammation in a rodent model of WBV, but the response of the low back and lumbar spine to WBV is unknown. A rat model of WBV was used to determine the effect of different WBV exposures on hind paw behavioral sensitivity and neuroinflammation in the lumbar spinal cord. Rats were exposed to 30 min of WBV at either 8 or 15 Hz on days 0 and 7, with the lumbar spinal cord a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 53 publications
(220 reference statements)
2
29
0
1
Order By: Relevance
“…To quantify colocalization of spinal sPLA2 in neurons, microglia and astrocytes, the total number of pixels positive for each of sPLA2 and MAP2, sPLA2 and Iba1, and sPLA2 and GFAP was separately quantified using a custom MATLAB script as previously described (Nicholson et al, 2012; Crosby et al, 2015b; Zeeman et al, 2016). Neuronal, microglial and astrocytic sPLA2 were each determined by dividing the total number pixels positive for sPLA2 and either MAP2, Iba1 and GFAP by the total number of positive pixels for sPLA2 (Zeeman et al, 2016) for each image and is presented as fold-change over normal. Each of neuronal, microglial and astrocytic sPLA2 expression was compared across groups using a two-way ANOVA with Tukey’s post hoc test (groupXday).…”
Section: Methodsmentioning
confidence: 99%
“…To quantify colocalization of spinal sPLA2 in neurons, microglia and astrocytes, the total number of pixels positive for each of sPLA2 and MAP2, sPLA2 and Iba1, and sPLA2 and GFAP was separately quantified using a custom MATLAB script as previously described (Nicholson et al, 2012; Crosby et al, 2015b; Zeeman et al, 2016). Neuronal, microglial and astrocytic sPLA2 were each determined by dividing the total number pixels positive for sPLA2 and either MAP2, Iba1 and GFAP by the total number of positive pixels for sPLA2 (Zeeman et al, 2016) for each image and is presented as fold-change over normal. Each of neuronal, microglial and astrocytic sPLA2 expression was compared across groups using a two-way ANOVA with Tukey’s post hoc test (groupXday).…”
Section: Methodsmentioning
confidence: 99%
“…Chronic inflammation is a known source of spine pain and novel methods are described to longitudinally track structural and inflammatory changes following injury . Neuroimmune cellular activation in response to whole body vibration can also induce spine injury and persistent pain . Bacterial infection in immune‐privileged IVDs can induce inflammation, induce IVD degeneration and result in modic‐like changes in the adjacent marrow in a model system providing some evidence for this provocative and intriguing back pain mechanism.…”
Section: Pathomechanisms Of Spine Painmentioning
confidence: 99%
“…5 Animal studies have shown that WBV can induce pain, exacerbate injury, and cause damage at the cellular level. 6,7 Carchietti et al 8 conducted a study on human subjects during helicopter transport and concluded that the level of vibration transmitted to the patient may cause bleeding in unstable bone fractures, such as those involving the pelvis. DeShaw and Rahmatalla showed that repetitive involuntary movements under WBV can cause discomfort at different locations on the human body, with more intense discomfort at the cervical and lumbar areas, 9 and that the level of discomfort was proportional to the intensity of the motion.…”
Section: Introductionmentioning
confidence: 99%
“…5 Animal studies have shown that WBV can induce pain, exacerbate injury, and cause damage at the cellular level. 6,7 Carchietti et al. 8 conducted a study on human subjects during helicopter transport and concluded that the level of vibration transmitted to the patient may cause bleeding in unstable bone fractures, such as those involving the pelvis.…”
Section: Introductionmentioning
confidence: 99%